Regular police officer perspectives on the Special Constabulary: An exploratory study. (10th February 2021) - Britton, Iain; Callender, Matthew; Cahalin, Kathryn; Knight, Laura
Abstract: A substantial body of research engaging volunteer Special Constables has reflected the importance for them of relationships and integration with their Regular, paid police officer colleagues. This article looks at this professional relationship from the other side, drawing upon 1, 382 responses to an online survey of Regular police officers undertaken across five police forces in England and Wales. Findings point to gaps in confidence in the adequacy of recruitment, training, and initial practice competency and scepticism on leadership and strategic direction. More positive findings reflect valuing the contribution and perceptions of positive relationships. This article identifies the need for police forces to engage and involve Regular officers more constructively with the Special Constabulary. The research has a broader relevance for cultural engagement and integration across the diversity of roles in the 'police family', both paid and volunteer.